2012
DOI: 10.1007/s00253-012-3960-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathway redesign for deoxyviolacein biosynthesis in Citrobacter freundii and characterization of this pigment

Abstract: Violacein (Vio) is an important purple pigment with many potential bioactivities. Deoxyviolacein, a structural analog of Vio, is always synthesized in low concentrations with Vio in wild-type bacteria. Due to deoxyviolacein's low production and difficulties in isolation and purification, little has been learned regarding its function and potential applications. This study was the first effort in developing a stable and efficient biosynthetic system for producing pure deoxyviolacein. A recombinant plasmid with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
(57 reference statements)
1
26
0
4
Order By: Relevance
“…10 Among these, the L-tryptophan-derived bisindoles, i.e. deoxyviolacein and the structurally analogous violacein, are attractive due to their antibacterial, 36,37 antifungal, 38 and anti-tumoral properties 37,39 and the possibility to produce them at gram scales with E. coli. 34,35 Numerous available genetic modules allow it to respond E coli.…”
Section: Introductionmentioning
confidence: 99%
“…10 Among these, the L-tryptophan-derived bisindoles, i.e. deoxyviolacein and the structurally analogous violacein, are attractive due to their antibacterial, 36,37 antifungal, 38 and anti-tumoral properties 37,39 and the possibility to produce them at gram scales with E. coli. 34,35 Numerous available genetic modules allow it to respond E coli.…”
Section: Introductionmentioning
confidence: 99%
“…Deoxyviolacein is a microbial metabolite that receives high interest due to its biological activity against tumors (Jiang et al, ), gram‐positive bacteria, and plant pathogenic fungi (Wang et al, ). Biosynthesis of this compound occurs naturally in different bacteria and involves a series of biochemical reactions that start from the precursor L ‐tryptophan and proceed through a cascade of enzymes encoded by the vioABCE operon (Hoshino, ).…”
Section: Introductionmentioning
confidence: 99%
“…E. coli has been engineered for metabolic production of drugs such as artemisinin, cinnamaldehyde, carbapenem, violacein, deoxyviolacein (dVio), etc., at industrial scales . Among these, the l ‐tryptophan‐derived bisindoles dVio and violacein are attractive due to their antibacterial, antifungal, and antitumoral properties and the possibility to produce them at gram scales . dVio is synthesized from endogenously produced l ‐tryptophan by expressing four enzymes, vioA, vioB, vioC, and vioE, in E. coli , genetically encoded as a vioABCE operon .…”
mentioning
confidence: 99%
“…During our initial experiments of dVio synthesis in liquid cultures, we observed that the drug remained within the bacteria and barely diffused to the surrounding medium (Figure S3, Supporting Information). This was attributed to dVio's poor water solubility, causing its aggregation in the bacterial cytosol. Solubilization and release of dVio from the bacteria was achieved by adding the nonionic surfactant Genapol C200 (Gen) to the medium.…”
mentioning
confidence: 99%